Pengaruh Pemberian Dosis KNO3 terhadap Pertumbuhan, Produksi, dan Serapan Kalium Tanaman Jagung Manis (Zea Mays Saccharata Sturt) - DARWIN H. PANGARIBUAN; SARNO SARNO; RISQI KURNIA SUCI (Fakultas Pertanian Universitas Udayana, 2017)
Effect of KNO3 on the Growth, Production, and Potassium Uptake on Sweet Corn (Zea Mays Saccharata Sturt). This study aimed to determine the effect of KNO3 dosage fertilizer on the growth, production and potassium uptake of sweet corn varieties Talenta. This research was conducted in December 2015 to February 2016. This study used a randomized block design with 6 treatments and 3 replications. The treatments were control, KNO3 fertilizer with a dose of 50 kg ha-1, KNO3 fertilizer with a dose of 100 kg ha-1, KNO3 fertilizer with a dose of 150 kg ha-1, KNO3 fertilizer with a dose of 200 kg ha-1 and KNO3 fertilizer with a dose of kg ha-1, The results showed that KNO3 fertilizer impacted on plant height, leaf number, leaf area index, dry weight, number of rows per ear, seed number per row, total production, and uptake of pottasium. KNO3 fertilizer treatment at a dose of 132 kg ha-1 gave the best result of growth, production and best potassium uptake. The use of KNO3 could be an alternative fertilizer for Potassium fertilization of sweet corn.